2022
DOI: 10.1002/mame.202200363
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Bionic Design and Performance Evaluation of Polyacrylonitrile Fiber@SBS Modified Binder

Abstract: The mechanical properties of fiber composites are greatly affected by the interfacial interactions between the fibers and matrix, and hence the study of interfacial properties becomes critical. This study demonstrates a simple and effective interfacial modification process using polydopamine (PDA) coating with ZnO nanorods to construct a multi‐scale bionic structure on the polyacrylonitrile (PAN) fiber, which is conducive to increasing the bonding area and enhancing the load transfer, thus boosting the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 51 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…FM can characterize the distribution of fibers and SBS in the asphalt binder 18 . Asphaltenes and aromatic hydrocarbons influence the diffusion of SBS in the asphalt binder 17 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…FM can characterize the distribution of fibers and SBS in the asphalt binder 18 . Asphaltenes and aromatic hydrocarbons influence the diffusion of SBS in the asphalt binder 17 .…”
Section: Resultsmentioning
confidence: 99%
“…FM can characterize the distribution of fibers and SBS in the asphalt binder. 18 Asphaltenes and aromatic hydrocarbons influence the diffusion of SBS in the asphalt binder. 17 Figure 15a shows that SBS polymer in SBS@MA is unevenly agglomerated, showing a dense distribution.…”
Section: Fm Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure 6F, the cone penetration and shear stress test results for each modified asphalt sample are presented to evaluate the shear rheological resistance of the modified asphalt. 55 It is observed that as the fiber content increases gradually from 0.5% to 1.5%, the cone penetration of the asphalt binder decreases, while shear strength increases. Furthermore, at the same fiber dose, the shear strength of the asphalt binder follows the order of ZIF-67-PDA-PET/SBS-MA > PET/SBS-MA > SBS-MA.…”
Section: Analysis Of Rheological Properties Of Asphaltmentioning
confidence: 94%
“…56 Notably, at ZIF-67-PDA-PET fibers doping level of 1.5%, a 3.6% increase in the softening point and a 26.23% enhancement in ductility compared to the original PET fiber-modified asphalt was observed, demonstrating improved high-temperature stability. 55 This improvement can be attributed to the ZIF-67-PDA interfacial layer, which provides the PET fibers with enhanced roughness and surface activity. Consequently, the fibers exhibit greater adsorption of light components, reinforcing the structural layer of fibers in contact with the asphalt, thereby enhancing stress transfer at the fiber-asphalt interface.…”
Section: Analysis Of Rheological Properties Of Asphaltmentioning
confidence: 99%